4b-6-12b-4=

Simple and best practice solution for 4b-6-12b-4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4b-6-12b-4= equation:


Simplifying
4b + -6 + -12b + -4 = 0

Reorder the terms:
-6 + -4 + 4b + -12b = 0

Combine like terms: -6 + -4 = -10
-10 + 4b + -12b = 0

Combine like terms: 4b + -12b = -8b
-10 + -8b = 0

Solving
-10 + -8b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -8b = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -8b = 0 + 10
-8b = 0 + 10

Combine like terms: 0 + 10 = 10
-8b = 10

Divide each side by '-8'.
b = -1.25

Simplifying
b = -1.25

See similar equations:

| 2x+3y=2772 | | x-25=5+11x | | K=-5/2 | | 3y-(-4y+3)=-17 | | (x-2)/6=(x+3)/9 | | 35-8x=22 | | 7(6+2)= | | -(5a+4)+1=2-(5a-1) | | -22.4+6x=75.5 | | t/-17.7=-12.7 | | -(2a-2)+3=3-(2a+5) | | 6(3-2)x=54 | | 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 | | 17/x+7 | | 7.6=p-6 | | -8|3-8k|=40 | | Ln(3x)+5=7 | | 2/7x14/3 |

Equations solver categories